Genome-Wide Identification, Evolution, and Expression of GDSL-Type Esterase/Lipase Gene Family in Soybean - Su, Hong-Gang; Zhang, Xiao-Hong; Wang, Ting-Ting; Wei, Wen-Liang; Wang, Yan-Xia; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Ma, You-Zhi; Xu, Zhao-Shi; Min, Dong-Hong (Frontiers in Plant Science, 2020)
GDSL-type esterase/lipase proteins (GELPs) belong to the SGNH hydrolase superfamily and contain a conserved GDSL motif at their N-terminus. GELPs are widely distributed in nature, from microbes to plants, and play crucial roles in growth and development, stress responses and pathogen defense. However, the identification and functional analysis of GELP genes are hardly explored in soybean. Here, a total of 194 GELP genes were identified and analyzed in the soybean genome, were arranged into 11 subfamilies (A-K) based on phylogenetic analysis. GmGELP genes are disproportionally distributed on 20 soybean chromosomes. Large-scale gene duplication events in the soybean genome contributed greatly to the expansion of the soybean GDSL gene family. The Ka/Ks ratios of more than 70% of duplicated gene pairs range from 0.1-0.3, indicating that most GmGELP genes are under purifying selection pressure. Gene structure analysis indicated that more than 74% of GmGELP genes are interrupted by 4 introns and composed of 5 exons in their coding regions, and closer homologous genes in the phylogenetic tree often have similar exon-intron organization. Further statistics revealed that approximately 37% of subfamily H members contain more than 4 introns, and about 23% of subfamily F members consist of less than 4 introns. For this reason, the two subfamilies were used to simulate intron gain and loss events, respectively. Furthermore, a new model of intron position distribution was established in current study to explore whether the evolution of multi-gene families resulted from the diversity of gene structure. Finally, RNA-seq data were used to investigate the expression profiles of GmGELP gene under different tissues and multiple abiotic stress treatments. Subsequently, 7 stress-responsive GmGELP genes were selected to verify their expression levels by RT-qPCR, the results were consistent with RNA-seq data.GmGELP28 was selected for further study owing to clear responses to drought, salt and ABA treatments. Transgenic Arabidopsis thaliana and soybean plants showed drought and salt tolerant phenotype. Overexpression of GmGELP28 resulted in the changes of several physiological indicators, which allow plants to adapt adverse conditions. In all, GmGELP28 is a potential candidate gene for improving the salinity and drought tolerance of soybean.